1999
DOI: 10.1021/ic980902p
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CO2 and H+ Reduction by Ni(cyclam)+ in Aqueous Solution. A Pulse and Continuous Radiolysis Study

Abstract: The reduction of CO 2 and H + by Ni(cyclam) + in aqueous solution was found to proceed by the reduction of Ni(cyclam)(CO 2 ) + or Ni(cyclam)(H) 2+ by Ni(cyclam) + . At ambient temperature the rate constants for the bimolecular reactions are 1.6 × 10 8 and 7.2 × 10 7 M -1 s -1 , respectively. Continuous γ-radiolysis studies have demonstrated nearly quantitative formation of CO from two Ni(cyclam) + at pH 5.2 under 1 atm of CO 2 and in the presence of formate. Under the same conditions, but at low CO 2 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 39 publications
(63 reference statements)
1
35
0
2
Order By: Relevance
“…The percentages of C, H, and N obtained from elemental analysis of Ni(cyclam)-PALA were 33.24 %, 6.21 %, and 12.31 %, respectively. UV/vis spectra ( Figure S4) of [Ni(cyclam)(pyCHO)](ClO 4 ) 2 and Ni(cyclam)-PALA displayed four transition bands, corresponding to 3 A 2g to 3 T 2g (680 nm), 3 A 2g to 3 T 1g (450 nm), and 3 A 2g to 3 T 1g (330 nm) transitions [5] for a d 8 metal ion in an octahedral environment (the bands at ca. An FTIR spectrum of the polymer (Figure S2) showed an C=N stretching vibration at 1606 cm À1 , proving Schiff's base condensation with the nickel complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of C, H, and N obtained from elemental analysis of Ni(cyclam)-PALA were 33.24 %, 6.21 %, and 12.31 %, respectively. UV/vis spectra ( Figure S4) of [Ni(cyclam)(pyCHO)](ClO 4 ) 2 and Ni(cyclam)-PALA displayed four transition bands, corresponding to 3 A 2g to 3 T 2g (680 nm), 3 A 2g to 3 T 1g (450 nm), and 3 A 2g to 3 T 1g (330 nm) transitions [5] for a d 8 metal ion in an octahedral environment (the bands at ca. An FTIR spectrum of the polymer (Figure S2) showed an C=N stretching vibration at 1606 cm À1 , proving Schiff's base condensation with the nickel complex.…”
mentioning
confidence: 99%
“…The rather broad aromatic peak indicates that the motions of these aromatic protons are slow, due to them being attached to the polymer backbone. UV/vis spectra ( Figure S4) of [Ni(cyclam)(pyCHO)](ClO 4 ) 2 and Ni(cyclam)-PALA displayed four transition bands, corresponding to 3 A 2g to 3 T 2g (680 nm), 3 A 2g to 3 T 1g (450 nm), and 3 A 2g to 3 T 1g (330 nm) transitions [5] for a d 8 metal ion in an octahedral environment (the bands at ca. 270 nm are due to charge-transfer transitions), suggesting axial coordination of 4-pyridine.…”
mentioning
confidence: 99%
“…[42] [Ni(cyclam)] 2 + (cyclam = 1,4,8,11-tetraazacyclotetradecane) is an efficient andselective electrocatalyst for the electrochemical reduction of CO 2 in acidic (pH 4) aqueouss olution,e specially with am ercury pool electrode, as shown by Beley et al in 1984. [43] Although it is known that mercury-adsorbed [Ni I (cyclam)] + is an active catalystf or CO 2 reduction in water, Kelly et al [39,44] tried to produce [Ni(cyclam)(CO 2 )] + through the reduction of [Ni(cyclam)] 2 + by e aq À or CO 2 C À ,f ollowed by CO 2 addition in aqueous solution containing CO 2 .A ss hown in Figure13, they found that the resulting intensity of the [Ni(cyclam)] + spectrum( l max = 380 nm) exhibitedasmalll inear decrease with [CO 2 ], which indicated the presenceo fa ne quilibrium, as shown in Equation (31). Assuming that the CO 2 adduct does not have any significant absorption in the l = 300-700 nm region, the K CO 2 for Equation (31) was estimated to be 16 m À1 (see Ta ble 3).…”
Section: Co 2 Reductionmentioning
confidence: 99%
“…For uses of the title compound, see: Kimura et al (1992); Liang et al (2002); Burrows et al (1992Burrows et al ( , 1988; Kelly et al (1999); Churchard et al (2010). For the synthesis of the ligand, see: Beck & Lang (2003); Beck et al (1998.…”
Section: Related Literaturementioning
confidence: 99%